Urban Innovation and Philanthropy, New Perspectives on the Columbia Market, London - Emeline Houssard (Angles)
Completed in 1868 by architect Alfred Darbishire, Columbia Market is an astounding philanthropic project undertaken by Baroness Georgina Burdett-Coutts on behalf of the impoverished neighbourhoods of London's East End. Celebrated as much for its grandiose neo-Gothic architecture as for its spectacular economic failure, it has almost never been studied beyond the scope of an architectural approach, usually monographic or narrowed down to its decorations (Pevsner 1952; Schmiechen and Carls 1999; Lewis 2012; Jones 2016). Firstly, this article refines the architectural analysis of the Columbia Market through a better consideration not only of its decorum but also of its structure. By doing so, it reveals Darbishire’s interest in other contemporary markets in London such as Covent Garden Market, Hungerford Market, Billingsgate Market and Spitalfields Market. Notwithstanding an outright economic collapse, Darbishire and Burdett-Coutt’s project is greeted with several echoes throughout Europe, of which this article offers the first comprehensive study. Mentioned in most of the contemporary journal articles, publications, and municipal reports devoted to neighbourhood covered markets, especially so in Berlin and Rome, it became an architectural model and a milestone in the European development of this type of building. Second, this article reconsiders Columbia Market as an exemplary case of the inherently urban character of neighbourhood covered markets, focusing on its implementation and insertion within a larger project associating urban facilities, housing and transportation. More than an isolated philanthropic gesture in this deprived area of London, Columbia Market emerged as an extension to Columbia Square’s dwellings, built in 1862 for Burdett-Coutts on the advice of Charles Dickens. Other less known urban facilities were later built in order to rationalize the neighbourhood and to respond to the hygienist principles of the time. In addition, several railway projects integrating Columbia Market were put forward between 1870 and 1890, revealing both the interest in a new approach to urban planning and the transportation problems specific to this typology.Considering the history of Columbia Market over the long term and the reasons for its failure thus contributes to a better understanding of its history and typology, as well as that of the neighbourhood and the city to which it belongs. The urban experiment associated with Columbia Market thus appears as a precursor of the programmes that only emerged in Europe after the Second World War, most notably the Lansbury Estate in London’s East End.